Use of a statistical model to follow the evolution of the probability of victory of para table tennis matches - Hamri, I.; Schipman, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Para-table tennis is an opposition sport where the mind and self-confidence have a predominant role. The purpose of this study is to estimate the probability of winning a para-table tennis match and to calculate the evolution of this probability at the end of each set.